Complete mitogenome assemblies from a panel of 13 diverse potato taxa - Achakkagari, S.R.; Bozan, I.; Anglin, N.L; Ellis, David; Tai, H.H.; Stromvik, M.V. (Informa UK Limited, 2021)
Mitochondrial DNA is maternally inherited and is shown to affect nuclear-cytoplasmic interactions in potato. Analyzing the mitogenome helps understand the evolutionary relationships and improve breeding programs in potato. We report complete mitogenome sequences from a panel of 13 potato accessions of various taxa. Each mitogenome has three independent circular molecules, except one of the S. bukasovii sample BUK2, which has a single circular molecule. Each mitogenome code for 37 non-redundant protein-coding genes, three rRNAs, 20 tRNAs, and 19 hypothetical open reading frames. Phylogenetic analysis reveals congruency between plastome and mitogenome phylogeny.